A graphene oxide-based fluorescent aptasensor for alpha-fetoprotein detection. Issue 32 (1st August 2016) - Zhang, Ya; Bai, Yunfeng; Feng, Feng; Shuang, Shaomin
Abstract : A sensitive and selective strategy for alpha-fetoprotein (AFP) detection was developed based on an aptamer/GO fluorescent biosensor. Abstract : A simple, rapid and sensitive method for the detection of alpha-fetoprotein was developed based on FAM-labeled aptamers and the fluorescence quenching ability of graphene oxide.